Meningkatkan Literasi Membaca Dengan Metode Cooperatif Learning di Kelas II pada Mata Pelajaran Bahasa Indonesia Melalui Media Pohon Literasi di SDN 080/VIII Sukadamai - Lestari, Lestari; Megawati, Megawati (Master of Pedagogy and Elementary School Learning, 2025)
This study aims to improve the reading skills of grade 2 students of SDN 080/VIII in Indonesian language subjects, the method used is litereation tree media. Based on the implementation of the pre-cycle in class 2 at the time of the research, it was found that the reading skills of grade 2 students of SDN 080 / VIII Sukadamai were very low. This can be seen from the symptoms that occur in learning, students' interest in reading is quite low, so students are still not fluent when reading. This study was conducted in October 2024, at SDN 080 / VIII Sukadamai with 19 students as subjects. This research uses the type of action study that describes statistical analysis in the classroom consisting of 4 stages, namely planning, implementing, observing and reflecting. The data collection techniques used in this study are observation (Observation), questionnaires, and performance tests (Performance). Based on initial observations obtained from the results of students' reading skills, only 9 students finished. After using the literacy tree media in the first cycle, 10 students had a 71% success rate. Then the method was improved in the second cycle, getting the results of 16 students' reading skills with a percentage of 85%. Therefore, it can be concluded that the use of literacy tree media can improve students' reading skills in grade 2 Indonesian language subjects at SDN 080 / VIII Sukadamai.